WACANA TANPA OSPEK, UNAS SAMBUT MAHASISWA BARU LEWAT CHARACTER BUILDING (Analisis Wacana Kritis pada Berita) - Adi Prakosa (Jurnal Ilmu dan Budaya, 2018)
Ospek and Character Building are two concepts offered by news writers to news readers. The Ospect has a spooky connotation. In fact, some students become victims of ospek activities, some even died. Character building has a convenient connotation. This research seeks to review the news entitled "Without Ospek, UNAS welcomes New Students Through Character Building". This news was published on August 3, 2016. The reason for the selection of this study object is based on the content of news reporting that the National University does not apply the Ospek in the admission of new students. While most other universities are still applying ospek. There is a new rule, ospek is not horror anymore. The rules of ospek have changed since the admission of new students in 2015/2016. The formulation of the problem in this study: "How to understand the discourse of news" Without Ospek, UNAS welcomes New Students Through Character Building "in unas.ac.id Edition 3 August 2016?" The theory that became the reference is Critical Theory. Subjects in the study are newsmakers "Without Ospek, UNAS welcomes New Students Through  Character Building", the division of Public Relations of National University. While the object of study is the news "Without Ospek, UNAS Welcomes New Students Through Character Building". In searching the data, the technique used is as follows: (1) content analysis to the news "Without Ospek, UNAS welcomes New Students Through Character Building", applied to obtain data in the form of news text; (2) in-depth interviews with newsmakers and news readers, applied to obtain data pertaining to discourse practice (news text); (3) literature studies on books, websites, scientific journals, research reports, documents, applied to obtain data regarding socio-cultural practices. The results show that the news reviewed is part of promotional activities in the admission of new students at the National University.